FORMS AND METHODS OF STATE SUPPORT AND REGULATION OF AGRICULTURAL PRODUCTION - Abdurashid Mamatkulov Vakhidovich (American Journals Publishing, 2024)
State support and regulation play pivotal roles in shaping the landscape of agricultural production, influencing productivity, sustainability, and economic viability. This article provides an in-depth exploration of various forms and methods of state intervention in agriculture, analyzing their impacts, effectiveness, and implications. Drawing on existing literature, empirical evidence, and policy analyses, this study offers insights into the mechanisms through which governments support and regulate agricultural activities. Through a comprehensive examination, it aims to inform policymakers, stakeholders, and researchers about the diverse strategies available for fostering a resilient and sustainable agricultural sector.
Keywords: State support, agricultural regulation, subsidies, incentives, agricultural production, policies.